SUBVERTING SOCIAL MEDIA - singh, sava saheli (AoIR Selected Papers of Internet Research, 2015)
We are forced to conform to the technological paradigms of social media platforms like Twitter, and the ostensibly democratic intention of "openness" of these platforms can actually serve to cause harm and enable harassers to target users. The very same features of Twitter that enable this harm can be subverted by communities as ways of reducing harm and calling attention to those causing harm. This paper highlights the conflict between the useful and harmful behaviors that are supported by Twitter, and how we have to shift our behaviors based on an evolving technological landscape.